Bay of Fundy Tides - Desplanque, Con; Mossman, David (Geoscience Canada, 2001)
Summary Eastern Canadian seaboard tidal characteristics result from a combination of diurnal (daily) and semi-diurnal (twice daily) tides, the latter mostly dominant. Because of the proportions of the Bay of Fundy, differences in tidal range are governed by near resonance with Atlantic tides. Exceptionally high Fundy tides result from this phenomenon, with upper reach tidal ranges commonly >15 m. Although Fundy tide curves are sinusoidal, tide prediction requires consideration of marked diurnal inequalities. Overlapping of the cycles of spring and perigean tides every 206 days results in an annual progression of 1.5 months in the periods of extra high tides. Strong tides can occur at all seasons, depending on the year. Considerable variation results throughout the year, with six distinct cycles recognized. Tides play a major role in erosionand in complex interactions among Fundyphysical, sedimentological, biological, and chemical processes. Recent observations on mud flat grain size alterations, over-deepening areas of the sea bed, andbenthic community changes, indicate changing environmental conditions in the Bay, possibly caused by increased hydro-dynamic energy in the system.